2005
DOI: 10.1152/ajpregu.00456.2004
|View full text |Cite
|
Sign up to set email alerts
|

Problems, possibilities, and pitfalls in studying the arterial baroreflexes’ influence over long-term control of blood pressure

Abstract: While there is no disputing the critical role of baroreflexes in buffering rapid changes in arterial pressure, their role in long-term pressure control has become an area of controversy. Recent experiments using novel techniques have challenged the traditional view that arterial baroreflexes are not involved in setting chronic arterial pressure levels. Resetting of the arterial baroreflex, often used as an argument against the arterial baroreflex playing a role in long-term pressure control is rarely complete.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…Therefore, the effect of DHB glucocorticoids to alter baroreflex gain could contribute to their pathophysiological effects on the cardiovascular system. The effects of DHB Cort to increase the baroreflex midpoint and reduce the reflex gain could also contribute to the development or maintenance of hypertension, although the role of the baroreflex in longterm regulation of arterial pressure is controversial (3,29,32,50). In summary, the results of the present study improve our understanding of the mechanisms that account for the increased cardiovascular disease risk imposed by elevated glucocorticoids and emphasize the importance of understanding the nature and mechanisms of glucocorticoid effects on central control of autonomic function.…”
Section: Perspectivesmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, the effect of DHB glucocorticoids to alter baroreflex gain could contribute to their pathophysiological effects on the cardiovascular system. The effects of DHB Cort to increase the baroreflex midpoint and reduce the reflex gain could also contribute to the development or maintenance of hypertension, although the role of the baroreflex in longterm regulation of arterial pressure is controversial (3,29,32,50). In summary, the results of the present study improve our understanding of the mechanisms that account for the increased cardiovascular disease risk imposed by elevated glucocorticoids and emphasize the importance of understanding the nature and mechanisms of glucocorticoid effects on central control of autonomic function.…”
Section: Perspectivesmentioning
confidence: 66%
“…The arterial baroreceptor reflex is an autonomic reflex that is important for the shortterm, and possibly long-term, regulation of arterial pressure (3,29,32,50). Studies from our laboratory have demonstrated that systemic administration of corticosterone (Cort) modulates baroreflex control of both renal sympathetic nerve activity and heart rate to increase the arterial pressure midpoint and decreases the reflex gain independent of changes in arterial pressure in rats (37, 40).…”
mentioning
confidence: 99%
“…16 The second tests short latency, including baroreflex mechanisms that resist (buffer) sudden rises or falls in blood pressure. 17,18 Analyzing the pattern of responses to each challenge reveals how vascular and cardiac mechanisms contribute to hemodynamic stability. We looked for unusual stress reactivity patterns as evidence of early underlying, "silent" cardiovascular dysfunction consistent with the known epidemiological risks associated with being born small, early, or to a smoker.…”
Section: Clinical Perspective P 1853mentioning
confidence: 99%
“…38 Thus, the low morning angiotensin II levels might serve as one explanation for the shift of the baroreflex curve in the present study. 32,40 This hypothesis, however, cannot be established with the present study, and it is well possible that the decrease in renin and angiotensin levels just reflects the passive consequence of nondipping but has no regulatory influence on baroreflex function.…”
Section: Discussionmentioning
confidence: 54%
“…31,32 It seems that the nocturnal sleep period uniquely allows the determination of this centrally driven set point, because wakefulness inevitably blurs or continuously modifies arterial baroreflex function. Recent animal studies highlighted the possibility of such a central nervous set point, 31 and our study suggests that such superordinated central nervous control of baroreflex function exists in humans as well.…”
Section: Discussionmentioning
confidence: 99%